2015
DOI: 10.1002/ana.24438
|View full text |Cite
|
Sign up to set email alerts
|

Sudomotor innervation in transthyretin amyloid neuropathy: Pathology and functional correlates

Abstract: ObjectiveAutonomic neuropathy is a major component of familial amyloid polyneuropathy (FAP) due to mutated transthyretin, with sudomotor failure as a common manifestation. This study aimed to investigate the pathology and clinical significance of sudomotor denervation.MethodsSkin biopsies were performed on the distal leg of FAP patients with a follow‐up duration of 3.8 ± 1.6 years. Sudomotor innervation was stained with 2 markers: protein gene product 9.5 (PGP 9.5), a general neuronal marker, and vasoactive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
6
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 49 publications
3
63
6
2
Order By: Relevance
“…This compares favorably with biopsies from other tissue sources including sural nerve, fat pad, and salivary gland biopsies. 11,34 In such studies, Congo red staining without birefringence was observed in the epidermis and diffusely throughout the sweat glands, which we not did observe in our disease controls. This strategy allowed us to assess larger portions of the sample with fewer sections, as well as to convincingly wtTTR protein stained prominently in healthy control epidermis (B, arrows), whereas there was little wtTTR staining in the epidermis from TTR-FAP subjects (D, arrow).…”
Section: Presence Of Amyloid In Skin Biopsiescontrasting
confidence: 52%
See 2 more Smart Citations
“…This compares favorably with biopsies from other tissue sources including sural nerve, fat pad, and salivary gland biopsies. 11,34 In such studies, Congo red staining without birefringence was observed in the epidermis and diffusely throughout the sweat glands, which we not did observe in our disease controls. This strategy allowed us to assess larger portions of the sample with fewer sections, as well as to convincingly wtTTR protein stained prominently in healthy control epidermis (B, arrows), whereas there was little wtTTR staining in the epidermis from TTR-FAP subjects (D, arrow).…”
Section: Presence Of Amyloid In Skin Biopsiescontrasting
confidence: 52%
“…The striking presence of endoneurial and dermal collagen amyloid that often engulfs dermal nerve fibers suggests that axonal loss might result from amyloid-induced compression and that arteriole involvement accelerates the injury through a superimposed ischemia. 11 Additionally, we observed that proximal thigh IENFD and SGNFD were reduced in TTR-FAP patients compared to age-/gender-matched controls. 9,38,39 Cutaneous Nerve Fiber Densities in TTR-FAP and TTR-noPN We observed that unmyelinated nerve fiber densities, including IENFD, SGNFD, and PMNFD, were markedly reduced at the distal leg in TTR-FAP patients.…”
Section: Presence Of Amyloid In Skin Biopsiesmentioning
confidence: 64%
See 1 more Smart Citation
“…Studies have also shown that skin biopsy can not only provide structural and pathological evidence of nerve degeneration, but also provide surrogate markers of function, thereby widening the applications of skin biopsy in assessing the involvement of the peripheral autonomic system and as a potential outcome measure in clinical trials. For example, reductions in sudomotor innervation correlated with autonomic symptoms, progressive disability and reduced performance in autonomic functional tests in 28 patients with familial amyloid neuropathy 138 . In 97 patients with diabetic neuro pathy, innervation of sweat glands correlated with glycated haemoglobin and BMI 139 .…”
Section: Stromamentioning
confidence: 98%
“…Patients with SFN followed for approximately 2.5 years showed progression of epidermal nerve fiber loss although healthy control subjects maintained stable nerve fiber densities [98]. Similarly, loss of epidermal nerve fibers can be seen in individuals with transthyretin familial amyloid polyneuropathy before large fiber involvement becomes evident [35, 116]. In patients followed longitudinally before, during, and after oxaliplatin chemotherapy, IENFD testing performed as well as a composite score of signs, symptoms, and nerve conduction results in assessing the progression of chemotherapy-induced peripheral neuropathy [29].…”
Section: Recommendationsmentioning
confidence: 99%